The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/er.6133
|View full text |Cite
|
Sign up to set email alerts
|

New insight on the open‐circuit voltage of perovskite solar cells: The role of defect‐density distribution and electric field in the active layer

Abstract: In this article, we study the J-V characteristic of a perovskite solar cell (PSC) prepared by the two-step method. PSCs were fabricated by methylammonium lead iodide using the sequential deposition method. We describe J-V curves using a modified dynamic electrical model based on an asymmetric electric field. In addition, we simulated the PSCs by solar cell capacitance simulator package to investigate the role of trap-density distribution in cell performance. The experimentally optimized device shows an enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…As shown in Figure 7B, it was found that the charge-recombination lifetime of the DASSA device (with fall time of 135 ms) was much longer than that of the DASSA without antisolvent device (with fall time of 21 ms). The reduced charge recombination is promoted by optimized morphology such as interconnected grains and a low number of pinholes as supported by the SEM/XRD images in the previous section as well as previous literature on transient measurements (Yu et al, 2016;Zarabinia et al, 2021;Tailor et al, 2020).…”
Section: Solar Cells Fabricated With Perovskite Films Deposited Via A...supporting
confidence: 67%
“…As shown in Figure 7B, it was found that the charge-recombination lifetime of the DASSA device (with fall time of 135 ms) was much longer than that of the DASSA without antisolvent device (with fall time of 21 ms). The reduced charge recombination is promoted by optimized morphology such as interconnected grains and a low number of pinholes as supported by the SEM/XRD images in the previous section as well as previous literature on transient measurements (Yu et al, 2016;Zarabinia et al, 2021;Tailor et al, 2020).…”
Section: Solar Cells Fabricated With Perovskite Films Deposited Via A...supporting
confidence: 67%
“…Compared with that of the PVK, the PL intensity of PVK/Cs:NiO x , PVK/CuInS 2, or PVK/Cs:NiO x /CuInS 2 is significantly weakened because CuInS 2 or Cs:NiO x /CuInS 2 can extract and transport carriers from PVK layer. Moreover, the PL intensity of the PVK/Cs:NiO x /CuInS 2 is less than the PVK/CuInS 2 , which demonstrates that double HEL of Cs:NiO x /CuInS 2 has stronger hole extraction and transport ability than the single HEL of CuInS 2 36‐38 …”
Section: Resultsmentioning
confidence: 97%
“…The intersite defects arise from the replacement of MA, Pb, and I ions, which lead to a variation in the open‐circuit voltage of the device as seen in Figure 7F. Open circuit voltage is high at low defect density, and V OC is very poor at high defect density (0.2 V at 10 19 cm −3 ) and further reduces to zero at N d = 10 20 cm −3 51 . The details are shown in Tables S5 and S6.…”
Section: Resultsmentioning
confidence: 99%
“…Open circuit voltage is high at low defect density, and V OC is very poor at high defect density (0.2 V at 10 19 cm À3 ) and further reduces to zero at N d = 10 20 cm À3 . 51 The details are shown in Tables S5 and S6.…”
Section: Samplementioning
confidence: 99%